2014
DOI: 10.1007/s10616-014-9742-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chemotherapy exposure prior to pregnancy on fetal brain tissue and the potential protective role of quercetin

Abstract: Cyclophosphamide (CYC) and doxorubicin (DOX) are among the most effective and widely used anticancer chemotherapeutic drugs. Potential chemopreventive and chemotherapeutic functions have recently been attributed to flavonoids. We hypothesized that Quercetin (QR) would protect against the toxic effects of chemotherapeutic agents applied prior to pregnancy. Rats were treated with the chemotherapeutic drugs CYC (27 mg/kg) and DOX (1.8 mg/kg) applied in a single intraperitoneal dose once every 3 weeks for 10 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 46 publications
(44 reference statements)
1
17
0
1
Order By: Relevance
“…In vitro and brain injury animal model studies have consistently revealed that QR exerts neuroprotective function through antagonizing oxidative stress. In the fetal brain, QR is able to suppress maternal chemotherapy induced oxidative stress (Dogan et al, 2015). Consistent with this observation, our results showed that QR potently suppressed oxidative stress induced by LPS exposure in fetal brain.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In vitro and brain injury animal model studies have consistently revealed that QR exerts neuroprotective function through antagonizing oxidative stress. In the fetal brain, QR is able to suppress maternal chemotherapy induced oxidative stress (Dogan et al, 2015). Consistent with this observation, our results showed that QR potently suppressed oxidative stress induced by LPS exposure in fetal brain.…”
Section: Discussionmentioning
confidence: 99%
“…QR (10 mg/kg/day, Alfa Aesar GmbH, Karlsruhe, Germany) was administered via oral gavage following LPS or saline injection. Dose of QR was determined according to a previous study (Dogan et al, 2015). Control rats were ip injected with 0.1 mL sterile saline.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…With respect to the research on the impact of quercetin on apoptosis, Kou [ 173 ] and Gibellini et al [ 174 ] found that quercetin in a dose-dependent manner induces apoptosis, arrest the cells at different cycles and block their growth in various cancer cells. In addition, several animal studies have also been conducted and they found the mechanisms of chemopreventive and therapeutic effects of quercetin [ 175 , 176 , 177 , 178 ]. The epidemiological studies also reported that the regular consumption of quercetin (1.01–31.7 mg/day) could reduce the ovarian cancer risk [ 179 ].…”
Section: Telomerase Inhibitors From Natural Productsmentioning
confidence: 99%